Modern Challenges for Oil and Gas Education - V. G. Martynov; V. N. Koshelev; A. V. Dushin (Высшее образование в России)
Today, in education in general and in higher education in particular, there is no more pressing problem than the organization of the educational process in the context of a pandemic that all universities in the world are facing. Also, there are no universal recipes for how to organize educational and scientific processes in a university without losing quality. The authors share their experience on how to restructure the work of teachers with students in the context of distance communication, organize the work of an educational portal, conduct training sessions, internships, state final certification, create motivational remuneration for the teaching staff. The article concludes that the challenges of the pandemic to higher education made it possible to find algorithms for interaction between students and teachers in the online environment, showed the need to improve the methodological qualifications of teachers, motivational and psychological support for participants in the educational process, accelerate the development of digital resources.